2012
DOI: 10.1097/inf.0b013e31822e68e6
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus-associated Hospitalizations Among Infants and Young Children in the United States, 1997–2006

Abstract: RSV hospitalization rates remained steady during 1997 to 2006 and were a substantial burden in the United States, especially among infants and young children. A safe and effective RSV vaccine is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
273
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(301 citation statements)
references
References 22 publications
17
273
3
8
Order By: Relevance
“…Although recent studies, most of which were retrospective assessments, have consistently shown RSV hospitalizations to be the highest in the first year of life, very few have dissected the exact age of RSV-specific hospitalizations more precisely. [4][5][6][13][14][15][16][17][18][19][20] For example, a retrospective, population-based study from Spain found that among children ,24 months old hospitalized with laboratory-identified RSV, 9% were ,1 month of age, similar to our findings; however, their rate of RSV hospitalizations among infants ,1 month of age was more than twice ours (31 per 1000 vs 13.5 per 1000, respectively). 19 Another study estimated a notably high annual rate of RSV-associated hospitalizations among infants #3 months old, 48.9 per 1000 children, which is more than twice the rate we found.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Although recent studies, most of which were retrospective assessments, have consistently shown RSV hospitalizations to be the highest in the first year of life, very few have dissected the exact age of RSV-specific hospitalizations more precisely. [4][5][6][13][14][15][16][17][18][19][20] For example, a retrospective, population-based study from Spain found that among children ,24 months old hospitalized with laboratory-identified RSV, 9% were ,1 month of age, similar to our findings; however, their rate of RSV hospitalizations among infants ,1 month of age was more than twice ours (31 per 1000 vs 13.5 per 1000, respectively). 19 Another study estimated a notably high annual rate of RSV-associated hospitalizations among infants #3 months old, 48.9 per 1000 children, which is more than twice the rate we found.…”
Section: Discussioncontrasting
confidence: 50%
“…19 Another study estimated a notably high annual rate of RSV-associated hospitalizations among infants #3 months old, 48.9 per 1000 children, which is more than twice the rate we found. 6 The differences between studies could result from actual differences in disease burden or from the use in database studies of ICD-9-CM-coded discharge diagnoses for RSV-associated syndromes such as bronchiolitis, because they are inaccurate indicators of RSV infection among young infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RSV infection rates are high and by age 2 years the majority of young children have experienced at least one infection (CDC, 2008(CDC, , 2013Hall et al, 2009;Mori et al, 2014;Nair et al, 2010;Stockman et al, 2012; Zhou et al, 2012). RSV infection in high-risk individuals, such as infants, young children, immunocompromised adults and the elderly, can manifest as serious pulmonary inflammatory disease including bronchiolitis and pneumonia (Hoffman et al, 2004;Moore et al, 2013;Openshaw & Chiu, 2013;Oshansky et al, 2009b;Psarras et al, 2004;Vicencio, 2010).…”
Section: Introductionmentioning
confidence: 99%